1989
DOI: 10.1002/dvg.1020100204
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of chorion formation in Drosophila melanogaster: I. The effects of one somatic‐specific and seven germ‐line‐specific mutations

Abstract: Eight X-linked recessive female sterile mutations, derived from a hybrid dysgenic screen of Drosophila melanogaster and representing eight distinct loci, have been characterized by genetic and ultrastructural analysis. Four have abnormal respiratory appendages, three have essentially normal appendages but show moderate defects in the endochorion, and one mutant, fs(1)ne1a, exhibits major defects in both the endochorion and the respiratory appendages. Germ line clones of all eight mutants were generated using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Chorion components of the fruit fly eggshell, for example, provide the embryo with protection from the physical environment, and disrupting their function causes female sterility [27]. Recently, proteomic techniques have identified Anopheles eggshell constituents, several of which we find to be specifically expressed in the ovary, making them favourable candidates for use in population control [28].…”
Section: Discussionmentioning
confidence: 99%
“…Chorion components of the fruit fly eggshell, for example, provide the embryo with protection from the physical environment, and disrupting their function causes female sterility [27]. Recently, proteomic techniques have identified Anopheles eggshell constituents, several of which we find to be specifically expressed in the ovary, making them favourable candidates for use in population control [28].…”
Section: Discussionmentioning
confidence: 99%
“…This locus encodes several transcription factors (92) and is known to mediate signaling by the steroid molecule ecdysone in other tissues during larval metamorphosis (93)(94)(95). Hypomorphic BR-C mutants result in smaller chorion dorsal appendages (91,96), and have been reported to reduce levels of chorion gene amplification (97), although the 50% reduction is modest compared with those of other amplification mutants. BR-C is also expressed in all stage 6 follicle cells (91).…”
Section: Developmental Control Of Amplificationmentioning
confidence: 99%
“…The spatially-specific regulation of chorion genes may be made possible by a genetic mechanism that coordinates the development of polarity in both the oocyte and the enveloping follicular epithelium. It has been suggested that the pattern of chorion gene expression may be controlled by cell -cell interactions between the germline cells (nurse cells and oocyte) and the somatic follicular epithelium (Parks and Spradling, 1987;Schupbach, 1987;Galanopoulos et al, 1989). At the anterior end, follicle cells participate in migrations at the onset of choriogenesis, to form the dorsal appendages and to close communication between the nurse cells and the oocyte.…”
Section: S36mentioning
confidence: 99%
“…The genetic evidence that many mutations in the germ line interfere with formation of the anterior chorion structures (e.g. Galanopoulos et al, 1989) suggests that the follicle cell migrations might follow local cues on the oocyte surface. Certainly, the anterior end of the oocyte has unique properties at that time, as exemplified by the anterior dorsal location of the nucleus (King, 1970), the perinuclear location offs(J)K10 transcripts (Haenlin et al, 1987) and the anterior cap of bicoid mRNA (Berleth et al, 1988).…”
Section: S36mentioning
confidence: 99%